2008
DOI: 10.1016/j.seizure.2007.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis in epilepsy patients and other chronic medically ill patients and the role of cerebral pathology in the onset of psychosis: A clinical epidemiological study

Abstract: This finding suggests that in the onset of psychosis in epilepsy patients, the role of cerebral pathology, especially localized left temporal and frontal, is of strong etiological importance. The following epilepsy endophenotypes should be explored as factors in vulnerability for psychosis as well: frequent and severe epileptic activity; and psychotic reactions to certain AEDs, such as Topiramate and Lamotrigine. Burden of disease does not seem to play an important role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The time periods over which the prevalence rates were calculated were as follows: 27 studies were for an unknown time period, 7 studies were lifetime prevalence studies, 21 studies were for more than 1 year and 3 studies were less than 1 year. Only 6 of the studies had control groups [31-36]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The time periods over which the prevalence rates were calculated were as follows: 27 studies were for an unknown time period, 7 studies were lifetime prevalence studies, 21 studies were for more than 1 year and 3 studies were less than 1 year. Only 6 of the studies had control groups [31-36]. …”
Section: Resultsmentioning
confidence: 99%
“…However, only 4 studies [31,34-36] were used for analysis because two of them [32,33] had no psychosis outcome in the control group so an odds ratio could not be calculated. The pooled odds ratio for risk of psychosis among people with epilepsy was 7.83.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[19,20] The hypothesis has been put forward based on the fact that the increased prevalence of autoimmune or chronic inflammatory diseases was before the onset of psychosis. [21] Psychosis is regarded as a well-known symptom in multiple sclerosis (MS), an autoimmune disease, especially in those patients with lesions in the periventricular white matter area. [22] Dickens [23] considered depression was more common in people with chronic inflammatory diseases such as rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the prevalence of POE has been estimated to be between 7% and 10% 1 . A 3-year epidemiological study held in The Netherlands revealed a prevalence of psychosis in 5.6% of epilepsy patients 6 . The overall evidence suggests that schizophrenia-like psychosis is believed to be 6 to 12 times more likely to occur in people with epilepsy than in the general population 7 …”
Section: Epidemiologymentioning
confidence: 99%